2005
DOI: 10.1007/s00417-004-1103-8
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal IOP fluctuation: not an independent risk factor for glaucomatous visual field loss in high-risk ocular hypertension

Abstract: IOP fluctuations were not an independent risk factor for the incidence of glaucomatous visual field loss in subjects with ocular hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 23 publications
2
75
1
7
Order By: Relevance
“…The results of our study also agree with those reported by Bengtsson and Heijl 16 as part of the Malmö Ocular Hypertension Study. In their investigation, high-risk ocular hypertensive patients were observed for 10 years as part of a prospective investigation to compare the rates of development of glaucomatous VF loss in patients treated with timolol versus a placebo.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study also agree with those reported by Bengtsson and Heijl 16 as part of the Malmö Ocular Hypertension Study. In their investigation, high-risk ocular hypertensive patients were observed for 10 years as part of a prospective investigation to compare the rates of development of glaucomatous VF loss in patients treated with timolol versus a placebo.…”
Section: Discussionsupporting
confidence: 93%
“…12 In the latter, 90 patients were examined every 3 months with office-hours diurnal tension curves and computerised perimetry. After a maximum follow-up to 17 years, 37 patients had developed glaucomatous visual field defects.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The purpose of the present study was to evaluate whether the amplitude of day-andnight IOP measurements [4][5][6][7][8][9][10][11][12] is an additional factor associated with the progression of glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 One long-term study that looked at diurnal IOP swings as an independent variable found that these fluctuations were not an independent risk factor for conversion to POAG. 40 Sleep laboratory experiments show that in all subjects supine and nocturnal IOPs rise, although the swing was lower in eyes with a higher baseline IOP. 41 However nocturnal (24 h) fluctuations may well contribute to the development of visual field progression in eyes with glaucoma damage, and measures to dampen such changes may offer additional protection.…”
Section: Commentmentioning
confidence: 93%